Situation Analysis as a Effort to Accelerate Stunting Reduction in Labuhan Batu Regency in 2022 - Asriwati Amirah; Juliandi Harahap; Rizki Ichwansyah (Journal of Universal Community Empowerment Provision, 2022)
Indonesia has set a target in accordance with the SDGs Program in 2030 in the health sector, namely through efforts to improve nutrition and health quality in combating the prevalence of stunting. The achievement of the SDGs goals must be prepared from now on by coordinating cross-sectoral. Over the last 20 years, the handling of the stunting problem has been very slow, globally, the percentage of children whose growth is stunted has decreased by only 0.6% per year since 1999. It is predicted that if this continues, 15 years later it is estimated that 450 million children will experience growth retardation or stunting. The contributing factor is suspected to be the lack of cross-sectoral roles in preventing stunting, so it is necessary to strengthen the role through convergence action to accelerate stunting reduction. The role of Universities as the Regency/City Assistance Implementation Team through the Stunting Reduction Acceleration Program in 10 loci in Labuhan Batu Regency with a 5-pillar approach, namely; (1) increasing commitment and leadership of the Village/Urban Government; (2) System strengthening and development, data, information, research and innovation; (3) communication of behavior change and community empowerment in terms of nutrition, healthy behavior, mutual cooperation and independence; (4) convergence of specific and sensitive interventions through a family approach caring for stunting; (5) food security at the level Individuals, Families and Communities through optimizing the use of local food ingredients. The factors that encourage the implementation of convergence actions to accelerate stunting reduction are the government's commitment, as well as the involvement of various parties, both from the health and non-health sectors.